Narrow band imaging complements eosinophilic esophagitis reference score in predicting inflammatory infiltration in patients with dysphagia - Truskaite, Kotryna; Vossen Engblom, Laura; Lindberg, Greger; Dlugosz, Aldona (Endoscopy International Open, 2025)
Magnifying endoscopy with narrow-band imaging (ME-NBI) is regularly used in neoplasia diagnostics although its use in assessment of esophageal inflammatory changes is uncommon. The aim of this study was to evaluate the efficacy of eosinophilic esophagitis reference score and ME-NBI signs in predicting inflammation using gastroscopy with dual focus in patients with dysphagia.We conducted a prospective cohort study in adults undergoing gastroscopy with esophageal biopsies because of dysphagia/food bolus impaction. Number of eosinophiles and lymphocytes were calculated per high-power field. We used logistic regression with forward stepwise selection to determine the most relevant predictors (endoscopic signs) of inflammation. To assess the predictive value of endoscopic signs for eosinophilic or lymphocytic infiltration, we calculated sensitivity, specificity, and predictive values.In total 219 patients (71.2% male) were enrolled to the study. Most frequent endoscopic findings were furrows (121/219, 55%), positive NBI signs (106/219, 48%), and edema (102/219, 47%). Logistic regression analysis showed that furrows and NBI signs were the most significant predictors of eosinophilic infiltration. Edema was the only significant predictor of lymphocyte infiltration.Positive NBI signs and furrows were the best predictors of eosinophile infiltration, whereas lymphocytic infiltration was predicted by edema. Given that NBI is already widely available, we encourage use of both white light and NBI in patients with suspected esophageal inflammation.
Keywords: Endoscopy Upper GI Tract; Eosinophilic esophagitis; Benign strictures; Diagnosis and imaging (inc chromoendoscopy, NBI, iSCAN, FICE, CLE)